SOCIAL REPRESENTATIONS OF BEING A TEACHER: AN ANALYSIS OF THE NATIONAL CURRICULUM GUIDELINES FOR INITIAL TEACHER EDUCATION (Interdisciplinary Studies Journal, 2025)
This article aimed to analyze evidence of social representations about being a teacher contained in the National Curricular Guidelines for Initial Higher Education Training for Basic School Education Teachers. Document Analysis was used as a methodological strategy to enable the collection, evaluation and interpretation of documents. The Theory of Social Representations was used as a theoretical-methodological framework for interpreting the document from a psychosocial perspective. In relation to teacher training, the text is anchored in the propositions of the references of the field itself. In relation to teacher training in the reflections of Gatti and Barreto (2009), Borges (2012) and Tardif (2014). The research prioritized a qualitative approach, as it prioritized a dynamic and totalizing method of interpretation of the reality found. The research analyzed a possible setback in relation to the offering of distance learning undergraduate courses since it makes it mandatory to carry out 50% of the disciplines in person. In addition, it excludes from the government the responsibility for the quality offered in teacher training, attributing to the students the responsibility for their development.
Keywords: Social Representations; Teacher Education; Distance Learning; Curriculum Guidelines